Functional analysis reveals effects of tobacco alternative oxidase gene (NtAOX1a) on regulation of defence responses against abiotic and biotic stresses. Issue 6 (22nd July 2009) - Zhang, Yi; Xi, Dongmei; Wang, Jian; Zhu, Dongfang; Guo, Xingqi
Abstract : Mitochondrial AOX (alternative oxidase) is the terminal oxidase of the CN (cyanide)-resistant alternative respiratory pathway in plants. To investigate the role of the tobacco AOX gene ( NtAOX1a ) (where Nt is Nicotiana tabacum ) under deleterious conditions which could induce ROS (reactive oxygen species) accumulation, we generated and characterized a number of independent transgenic tobacco ( N. tabacum ) lines with altered NtAOX1a gene expression and AP (alternative pathway) capacity. AOX efficiently inhibited the production of low-temperature-induced H2 O2 and might be a major enzyme for scavenging H2 O2 at low temperature. Furthermore, NtAOX1a may act as a regulator of KCN-induced resistance to TMV (tobacco mosaic virus) through the regulation of H2 O2 . Notably, a moderate accumulation of H2 O2 under the control of NtAOX1a was crucial in viral resistance. Analysis of seed germination indicated an important role for NtAOX1a in germination under H2 O2 -induced oxidative stress when the CP (cytochrome pathway) was inhibited. These results demonstrate that NtAOX1a is necessary for plants to survive low temperature, pathogen attack and oxidative stress by scavenging ROS under these adverse conditions when the CP is restricted.